Effects of irradiation on microbiological safety and physicochemical properties of dry pet food - Dongbin, P.; Sethukali, A.; Minwoo, C.; Jae-Kyung, K.; Hyun Jung, L.; Cheorun, J. (Korean Society of Animal Science and Technology, 2024)
The objective of this study was to investigate the effects of electron beam (EB) and X-ray (XR) irradiation on dry pet food during long-term storage. The samples were irradiated with EB and XR at doses of 0, 2.5, 5, 10, and 20 kGy, and their microbial safety and quality/oxidation properties were analyzed over 56 days under storage conditions of 25 C and 70% relative humidity. As a result, total aerobic bacteria (TAB) and yeasts and molds (YM) significantly decreased as the doses of EB and XR increased. When treated with 10 kGy for both irradiations, no bacteria were detected in the dry pet food, and this effect remained during the 56-day storage period. While EB and XR were effective in reducing aflatoxin B1 (AFB1) in solution, they showed limited effect on dry pet food. On the other hand, changes in quality traits such as proximate compositions, pH, water activity, color, and volatile basic nitrogen due to EB and XR were negligible. However, both types of irradiations induced lipid and protein oxidation in dry pet food. Also, a significant increase was observed in oxidation- related volatile compounds such as hydrocarbons, aldehydes, and ketones with EB and XR treatment, which suggested these changes could potentially impact the flavor of the dry pet food. The current findings confirm the efficient microbial reduction of dry pet food by EB and XR and the consequent changes in quality and oxidative properties. Future research should focus on sensory evaluations to understand the implications of these oxidized substances on pet preferences and explore potential methods to mitigate negative effects.
Keywords: Dry pet food; Irradiation; X-ray; Electron beam; Microbial safety; Oxidation